Estratégia de desenvolvimento econômico local: o caso do Município de Terra Roxa-PR - Willers, Ednilse Maria (2006)
The objective of this research was to analyze and to define a strategy of economic development that consolidates the economic emergency of Terra Roxa City - PR. Based on the theoretical premise of Hirschman (1974, 1996), in which the industrial expansion is a consequence of the economic development and the local is becoming the space of reference of strategic actions stimulating this expansion, the causes of the economic emergency of Terra Roxa were identified. The results of this research evidenced that its emergency is a consequence of the industrial base formed by micro, small and medium companies that are specialized in the branch of infantile confections. This industrial base has been responsible for the changes in the productive structure of the city, from urban-agricultural to urban-industrial, producing a sequence of events, stimulators of the local economy. As final result of this research, a strategy of economic development for the base was proposed. This strategy aims to the consolidation of the industrial base of infantile confections in Terra Roxa, stimulating the necessary structural changes to the productive chains that will lead, with the times, the economic development of the city.